2009
DOI: 10.1089/aid.2008.0219
|View full text |Cite
|
Sign up to set email alerts
|

Appreciating HIV Type 1 Diversity: Subtype Differences in Env

Abstract: Human immunodeficiency virus type 1 (HIV-1) group M is responsible for the current AIDS pandemic and exhibits exceedingly high levels of viral genetic diversity around the world, necessitating categorization of viruses into distinct lineages, or subtypes. These subtypes can differ by around 35% in the envelope (Env) glycoproteins of the virus, which are displayed on the surface of the virion and are targets for both neutralizing antibody and cell-mediated immune responses. This diversity reflects the remarkabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
80
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(85 citation statements)
references
References 126 publications
(111 reference statements)
5
80
0
Order By: Relevance
“…[22][23][24][25][26][27][28] Sequence variation within the V1/V2 loops alters neutralization resistance and viral escape is associated with V2 loop mutations. [29][30][31][32][33] Compared to viruses circulating in chronically infected persons, transmitted viruses (subtypes A and C) appear to have shorter V1/V2 regions and fewer N-linked glycosylation sites. 30,[34][35][36] The V2 loop contains a putative a 4 b 7 integrin binding motif (LDI/V) at amino acid (aa) residues 179-181 (HBX2 numbering system) that was shown to interact with the gut mucosal homing receptor.…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24][25][26][27][28] Sequence variation within the V1/V2 loops alters neutralization resistance and viral escape is associated with V2 loop mutations. [29][30][31][32][33] Compared to viruses circulating in chronically infected persons, transmitted viruses (subtypes A and C) appear to have shorter V1/V2 regions and fewer N-linked glycosylation sites. 30,[34][35][36] The V2 loop contains a putative a 4 b 7 integrin binding motif (LDI/V) at amino acid (aa) residues 179-181 (HBX2 numbering system) that was shown to interact with the gut mucosal homing receptor.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, although the majority of subtype C Envs has been shown to use CCR5 and rarely switch to CXCR4 tropism (2,14,18), this is the first study to evaluate the ability of primary subtype C Envs from chronically infected individuals and their acutely infected partners to utilize different levels of receptor and coreceptor. The requirement for high CCR5 levels by subtype C Envs is consistent with reports that infectivity by macrophage-tropic subtype B primary isolates are highly dependent on this coreceptor (20).…”
mentioning
confidence: 99%
“…While the WITS cohort consisted of clade B HIV-1-infected women from the United States, the BAN cohort of women from Malawi were infected with clade C HIV-1 strains. Interclade amino acid differences in HIV Env glycoproteins can be as high as 35% and influence the genetic selection of different viral strains and their interactions with their host's immune response (14).…”
Section: Discussionmentioning
confidence: 99%
“…S1 in the supplemental material). Furthermore, studies of V3 among different clades have revealed that the clade C V3 domain is relatively more conserved than that of clade B, as measured by the ratio of nonsynonymous to synonymous substitutions in V3 (14). In addition, the amino acid motifs of a highly conserved turn region of V3 differ between clades B and C (14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation